Proces vzniku rozhodnutí Ústavního soudu ČR - Jan Hořeňovský; Jan Chmel (Časopis pro Právní Vědu a Praxi, 2015)
The Constitutional court is the key institution which is authorized to protect the fulfilment of constitution. It is important to realize that the constitutional law is full of abstract words with many possible meanings and therefore the role of interpreters – judges - is extremely significant, as well as the process of decision making. The authors analyse the second aspect of the Constitutional court decision making: the process that leads to the final decision and the factors that may influence the process. The basic information can be found in an appropriate statute of the Court. The authors however try to focus rather on “law in action” than “law in book”. In the article, they therefore introduce the decision-making process from the perspective of judges and their assistants. They compose the mosaic consisting of many different points of view with the hope that result reflects the reality. Hopefully, the article may help the academics as well as practicing lawyers to understand the constitutional decision making.